DEVELOPING STUDENTS' DESCRIPTIVE READING SKILLS AND CRITICAL THINKING THROUGH THE SCAFFOLDING STRATEGY USING GOOGLE WORKSPACE FOR EDUCATION (GWE) - Umardani, Rudy; Saehu, Andang; Zuhairi, Aminudin (Universitas Tanjungpura, 2024)
The use of technology remains a need to integrate into the teaching-learning process. Meanwhile, the students are still weak in reading skills with their low critical thinking capacity and engage more activities not being tied and integrated into the learning process at school. The aim of this study was to explain the effectiveness of the scaffolding strategy using GWE on the students